Digital Orientation and Sustainable Business Performance : The Mediating Role of Digital Marketing Strategy - Ni Made Intan Kusumasari; Putu Ayu Trisna Febrianty; Dhea Fitrisia; Christina Ayu Maha Dewi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Digitalization of marketing is a strategy that can be implemented by wood crafts MSMEs to increase competitiveness and business entry in the current era. This study aims to examine and explain the role of digital marketing strategies in mediating the influence of digital orientation on sustainable business performance. The population of this study is wood crafts MSME business actors in Bali who have adopted digital strategies in the last three years. The number of samples used was 90 wood crafts MSME actors in Bali using the purposive sampling method. The analysis technique used was Path Analysis using SEM PLS. The results of the study showed that digital orientation had an effect on business sustainability performance, digital orientation had an effect on digital marketing strategies, and digital marketing strategies also had an effect on business sustainability performance. Digital marketing strategies can partially mediate the effect of digital orientation on sustainable business performance. Therefore, wood crafts MSMEs in Bali need to pay attention to and increase the intensity of implementing digital marketing strategies to improve business sustainability performance.